1985
DOI: 10.1177/070674378503000515
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Obsessive Psychosis? Aetiological and Prognostic Factors of an Atypical Form of Obsessive-Compulsive Neurosis

Abstract: The study explores whether an atypical form of obsessional illness can be delineated and separated from the conventional form of obsessive-compulsive neurosis (OCN). From a group of 45 obsessive patients, 8 were selected on the basis of 3 criteria: presence of a severely debilitating main obsessive symptom; bordering on the delusional; no schizophrenic symptoms. Assessment and outcome measures included the Psychiatric Questionnaire, the Leyton Obsessional Inventory, Fear Survey Schedule, and IPAT Self-Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
2
8

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 12 publications
9
45
2
8
Order By: Relevance
“…Patients with OCD have been observed to "…present a continuum of strength of belief in the senselessness of their obsessions and compulsions" [68]. Insight has been noted to vary on a continuum that ranges from good insight to delusional thinking [69][70][71], although more recent empirical data indicate that insight may be poor in OCD but is rarely absent [11]. This dimensional view of insight is supported by clinical observations that it can be difficult to distinguish between different levels of insight in OCD and that insight may alternate and depend on the situation [68].…”
Section: Should Delusional and Nondelusional Forms Of Obsessive-compumentioning
confidence: 99%
“…Patients with OCD have been observed to "…present a continuum of strength of belief in the senselessness of their obsessions and compulsions" [68]. Insight has been noted to vary on a continuum that ranges from good insight to delusional thinking [69][70][71], although more recent empirical data indicate that insight may be poor in OCD but is rarely absent [11]. This dimensional view of insight is supported by clinical observations that it can be difficult to distinguish between different levels of insight in OCD and that insight may alternate and depend on the situation [68].…”
Section: Should Delusional and Nondelusional Forms Of Obsessive-compumentioning
confidence: 99%
“…In 1903, Janet classified BDD within a group of syndromes similar to OCD, referring to BDD as "obsession with shame of the body." More recently, Solyom et al [1985] suggested that BDD may be a type of "obsessive psychosis"-an atypical and more malignant form of OCD. During the DSM-IV development process, consideration was given to classifying BDD in the same section of DSM-IV as OCD; however, this change was not made because of a lack of research examining their similarities and differences [Phillips and Hollander, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…These include: obsessive-compulsive disorder with psychotic features [5], obsessive psychosis [8], obsessive-compulsive psychosis [15] and schizo-obsessive disorder [16].…”
mentioning
confidence: 99%